Analisis Tafsir Qs. Al-Takasur Dan Implementasinya Dalam Dinamika Kehidupan Modern - Ashabul Kahfi; Achmad Abubakar; Muhammad Irham (LPPM IAIN Sorong, 2024)
Surah al-Takasur, the 102nd surah in the Qur'an, warns about the dangers of worldly preoccupation and the importance of awareness of life after death. This research aims to explore QS. al-Takasur to find out its implementation in modern life. The research method is descriptive qualitative with a focus on literature study. The research findings show that preoccupation with wealth and pride in it can distract people from worshiping Allah, until death. Allah's warning in al-Takasur reminds people not to get caught up in worldly competition, because in the end, all worldly pleasures will be held accountable. This study emphasizes the importance of understanding and applying the Qur'an's spiritual message in facing the challenges of modern times.